Deficiency of the anti-ageing hormone Klotho as a potential predictor of coronary artery disease. Issue 2 (2018) - Zhu, Zhanfang; Xu, Lei; Yang, Jin; Zhuang, Penghui; Yu, Min; Lei, Jiang; Hu, Xin; Hu, Li; Wang, Qingyu; Wang, Junkui; Yu, Qi; Liu, Fu-Qiang
No abstract available